Medical applications based on nanotechnology - Manaj, L.; Johnson, L.; Punz, E.; Joubert, I.A.; Geppert, M.; Himly, M. (Open Schools Journal for Open Science, 2020)
Poly-lactic-co-glycolic acid can form nanoparticles which can be applied in nanomedicine as delivery vehicle for therapeutic agents. Here the aim is to reduce negative side-effects and to obtain higher local concentrations at the site of action. This work is about determining the binding-capacity of PLGA nanoparticles to several substances, applying a small set of model proteins. Our aim was to find out, whether PLGA nanoparticles can transport drugs in order to make drug targeting in medicine easier. This would show us a new section of medicine with new ways of therapy methods.